Tingkat Kesuburan Perairan Berdasarkan Plakton dan Nutrien Serta Kualitas Air di Perairan Laut Merauke Provinsi Papua - Basa T. Rumahorbo; Janpiter Manalu; Kristoper A. A. Manalu (Cenderawasih University, 2021)
The abundance of plankton plays a very important role in determining the fertility of waters as a primary producer in waters. The abundance of plankton in water is generally related to the nutrient content in the water. This study aims to analyze the fertility level of Merauke sea waters based on the abundance of plankton and physical-chemical conditions in Merauke sea waters. Water samples were taken at 25 stations using water samples. showed that the abundance of plankton in Merauke seawater was high. The abundance of phytoplankton varied from 4,047,547 – 1,053.078 ind/m3/station. The dominating group is the Bacilliophyceae, the diversity index (H') is low <1, the uniformity is almost 0, the dominance index is low, while zooplankton is also classified as high with an abundance ranging from 5,500 – 460,281 ind/m3/ station Physical and chemical conditions of sea water such as temperature including homogeneous, namely between 25.950 – 27.580 C, low brightness 0 – 2 m, high turbidity 2.89 – 730 NTU, pH is homogeneous between 7.06 – 8.11, very high DO is between 8.00 – 9.55 mg/L . while the nutrient in the form of phosphate is quite high